Delayed denervation-induced muscle atrophy in Opg knockout mice - Zhang, Mingming; Chen, Ming; Li, Yi; Rao, Man; Wang, Duanyang; Wang, Zhongqi; Zhang, Licheng; Yin, Pengbin; Tang, Peifu (Frontiers in Physiology, 2023)
Recent evidence has shown a crucial role for the osteoprotegerin/receptor activator of nuclear factor κ-B ligand/RANK (OPG/RANKL/RANK) signaling axis not only in bone but also in muscle tissue; however, there is still a lack of understanding of its effects on muscle atrophy. Here, we found that denervated Opg knockout mice displayed better functional recovery and delayed muscle atrophy, especially in a specific type IIB fiber. Moreover, OPG deficiency promoted milder activation of the ubiquitin-proteasome pathway, which further verified the protective role of Opg knockout in denervated muscle damage. Furthermore, transcriptome sequencing indicated that Opg knockout upregulated the expression of Inpp5k, Rbm3, and Tet2 and downregulated that of Deptor in denervated muscle. In vitro experiments revealed that satellite cells derived from Opg knockout mice displayed a better differentiation ability than those acquired from wild-type littermates. Higher expression levels of Tet2 were also observed in satellite cells derived from Opg knockout mice, which provided a possible mechanistic basis for the protective effects of Opg knockout on muscle atrophy. Taken together, our findings uncover the novel role of Opg in muscle atrophy process and extend the current understanding in the OPG/RANKL/RANK signaling axis.